Pollinator Specific Richness and Their Interactions With Local Plant Species: 10 Years of Sampling in Mediterranean Habitats. Issue 4 (13th June 2020) - Ropars, Lise; Affre, Laurence; Aubert, Matthieu; Fernandez, Catherine; Flacher, Floriane; Genoud, David; Guiter, Frédéric; Jaworski, Coline; Lair, Xavier; Mutillod, Clémentine; Nève, Gabriel; Schurr, Lucie; et al.
Abstract: In the context of global pollinator decline, little is known about the protection status and ecology of many species. This lack of knowledge is particularly important for Mediterranean protected areas that harbor diverse pollinator communities and are subject to considerable anthropogenic pressures. Calanques National Park (85 km 2 ), which is located near Marseille (France), is dominated by Mediterranean low-vegetation habitats, such as phrygana and scrublands. These habitats offer favorable conditions for pollinator species due to the important amount of floral resources. Within a 10-yr period, we recorded bee (Hymenoptera: Apoidea: Anthophila), hover fly (Diptera: Syrphidae), and bee fly (Diptera: Bombyliidae) species and their interactions with the local flora through 10 field campaigns. We caught 250 pollinator species, including 192 bees, 38 hover flies, and 20 bee flies, for a total of 2, 770 specimens. We recorded seven threatened bees (six near threatened and one endangered). Among the bee species, 47.9% were below-ground nesting species, and 54.7% were generalist species. Analysis of the pollination network showed that generalist and specialist pollinators do not share the same floral resources. The Cistaceae plant family (Malvales: Cistaceae) acted as a central node in the plant–pollinator network, interacting with 52 different pollinator species, which shows the importance of large open flowers that could be easily visited by both short and long-tongued pollinators in Mediterranean habitats. The occurrence of pollinator species and their ecological traits should strongly contribute to reinforcing the available information to provide or ameliorate the conservation statuses determined by IUCN Red List.